Penerapan Play Therapy Dalam Pendampingan Psikologis Pada Remaja Di Panti Asuhan Putra Muhammadiyah Medan - Merri Hafni; Rahmi Lubis (Universitas Medan Area, 2022)
The Putra Muhammadiyah Orphanage has 49 boys. Where there are 6 children aged 12 sd. 15 year old who was abused by his caregiver. In general, the problems faced by the children of this orphanage are lack of self-confidence and low motivation to learn. The problem experienced by the Muhammadiyah Putra Orphanage is the experience of sexual violence experienced and has not received psychological treatment. The purpose of this service activity is to provide sexual education related to the prevention and handling of sexual harassment to adolescent residents of the Medan Muhammadiyah Putra Orphanage. The method used in this research is the lecture method and the discussion method. Sexual psychoeducation activities are carried out as the first step of the psychological assistance process in the play therapy approach. Based on the results obtained, it can be stated that psychoeducational materials are able to increase adolescent knowledge about aspects of sexuality.